Business Development Strategy “COFRESH” Product Using Business Model Canvas (BMC) and SWOT Analysis - Nita Kuswardhani; Rizki Agustian; Melinda Lady Plus (Universitas Darussalam Gontor, 2020)
CoFresh (Coffee Fresh) is an innovative odor removal product made from compacted robusta coffee powder, small in size with a diameter of ± 2 cm. This product is suitable for use as an air freshener. CoFresh is a new product emerging on the market that requires a reliable business development strategy. A lot of competition is a challenge to develop the CoFresh business. This research was conducted to determine the CoFresh business development strategy using BMC, SWOT analysis and Quantitative Strategic Planning Matrix (QSPM). BMC is analyzed based on customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, cost structure. The results of the EFE matrix calculation show that the CoFresh business is in a position to grow and develop. Meanwhile, the most dominant strategy in developing and improving marketing is to use an online marketing platform (IT based) and cooperate with coffee shops to promote products